The true meaning of jihad - Abd Razak, Dzulkifli (2006)
If someone still insists on framing jihad in the language of war, then it is the war with oneself — as a greater spiritual struggle in pure faith for the good of all humankind. THE international community might not have realised that for three weeks now a jihad has been waged involving the largest number of Muslims worldwide. And if this unique phenomenon has gone unnoticed, it is because there was not a single drop of blood spilled during this period, discounting those instigated by the "war of terrorism" linked to the socalled "jihadists". The question then is, despite the involvement of billions of jihadists — to borrow the violentladen insinuation — how is it that the monthlong jihad has remained quiet and peaceful? The answer is simply because thus far, the version of jihad made popular has been vulgarised.